Enhancing photocatalytic hydrogen peroxide generation by tuning hydrazone linkage density in covalent organic frameworks - Avanti Chakraborty; Akhtar Alam; Uttam Pal; Archisman Sinha; Subhadip Das; Tanusri Saha-Dasgupta; Pradip Pachfule (Nature Communications)
Abstract The conversion of solar energy into chemical energy or high-value chemicals has attracted considerable research interest in the context of the global energy crisis. Hydrogen peroxide (H2O2) is a versatile and powerful oxidizing agent widely used in chemical synthesis and medical disinfection. H2O2 also serves as a clean energy source in fuel cells, generating electricity with zero-carbon emissions. Recently, the sustainable production of H2O2 from water and oxygen using covalent organic frameworks (COFs) as photocatalysts has attracted considerable attention; however, systematic studies highlighting the role of linkages in determining photocatalytic performance are scarce. Under these circumstances, herein, we demonstrate that varying the imine and hydrazone linkages within the framework significantly influences photocatalytic H2O2 production. COFs with high-density hydrazone linkages, providing optimal docking sites for water and oxygen, enhance H2O2 generation activity (1588 μmol g−1 h−1 from pure water in the air), leading to highly efficient solar-to-chemical energy conversion.